Intelligent information technologies and applications - Sugumaran, Vijayan 1960- (IGI Pub., 2008)
"This book provides cutting-edge research on the modeling, implementation, and financial, environmental, and organizational implications of this dynamic topic to researchers and practitioners in fields such as information systems, intelligent agents, artificial intelligence, and Web engineering"--Provided by publisher.